Ab initio modelling of spin relaxation lengths in disordered graphene nanoribbons - Rojas, Wudmir Y.; Villegas, Cesar E. P.; Rocha, Alexandre R. [UNESP] (Royal Society of Chemistry (RSC), 2019)
The spin-dependent transport properties of armchair graphene nanoribbons in the presence of extrinsic spin-orbit coupling induced by a random distribution of nickel adatoms is studied. By combining a recursive Green's function formalism with density functional theory, we explore the influence of ribbon length and metal adatom concentration on the conductance. At a given length, we observed a significant enhancement of the spin-flip channel around resonances and at energies right above the Fermi level. We also estimate the spin-relaxation length, finding values on the order of tens of micrometers at low Ni adatom concentrations. This study is conducted at singular ribbon lengths entirely from fully ab initio methods, providing indirectly evidence that the Dyakonov-Perel spin relaxation mechanism might be the dominant at low concentrations as well as the observation of oscillations in the spin-polarization.